The 2007/8 global financial crisis : a decade on - Schaling, Eric, 1962-; Mitchell, Clare (London : Wits Business School, 2018)
The case provides an overview of the causes of the global financial crisis of 2007 to 2008 and the responses taken by the U.S. government in the short term and the new regulation implemented, namely the Dodd-Frank Act, to ensure that the crisis would not happen again. Students are invited to consider how the financial market in the U.S. has changed in the decade after the crisis and whether current financial regulation will be sufficient to prevent another crisis.
Originally Published In Schaling, E., & Mitchell, C. (2018). The 2007/8 Global Financial Crisis: A Decade On. WBS-2018-14. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United States; Global Financial Crisis, 2008-2009.